Pemodelan kondisi hidrodistilasi minyak atsiri jahe merah (Zingiber officinale var. Roscoe) dengan menggunakan Response Surface Methodology - Annissa Ramadhanti; Sarifah Nurjanah; Asri Widyasanti; Nurul Ainina (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Red ginger contains volatile components that are essential oils. Essential oils can be obtained through the distillation method. Hydrodistillation is a method of distillation that involves providing direct contact between the materials and water at a high temperature, which is influenced by several factors, including time and the solvent feed ratio (SF ratio). This study aimed to determine the best conditions for high yields and essential oil quality using SNI No. 06-1312-1998 as a reference. The research method used was experimental research, and optimization was carried out using Response Surface Methodology (RSM) with CCD design. The treatments for distillation were time (2 hours, 4 hours, and 6 hours) and solvent feed (SF) ratio (8:1, 10:1, and 12:1). The parameters observed were yield, residual solvent content, specific gravity, refractive index, and acid number. The results showed that the time and SF ratio variables had no significant effect on the yield but had a significant effect on the residual solvent content. The optimization process resulted in a time of 6 hours and a solvent volume of 720 ml (ratio 1:12), yielding 0.14 with a residual solvent content of 3,557%. The characteristics of the essential oils produced were 0.8794 for the specific gravity, 1.473 for the refractive index, and 2.13 for the acid number. Red ginger essential oil met the requirements of SNI ginger oil on the parameters of specific gravity and refractive index.